2017
DOI: 10.5120/ijca2017913404
|View full text |Cite
|
Sign up to set email alerts
|

Sales Performance Management System

Abstract: An overwhelming amount of data is produced by an active sales team who store all this data in the form of handwritten notes, excel spreadsheets, text documents, or by memorizing it. The consequence of this is misplaced details, inconsistent follow up of meetings, and prioritising customers based on assumptions rather than facts.Additionally, your customers may resolve their queries using different communication platforms, such as phone, email, and social media. Hence, if we don't have a standard platform for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This eliminated another 18 studies (Table 2). Habibi, Hamilton, Valos, and Callaghan (2015), Hofacker, Malthouse, and Sultan (2016), Lin, Swarna, and Bruning (2017), Lindsey-Mullikin and Borin (2017), Marolt, Pucihar, and Zimmermann (2015), Ioanid, Militaru and Mihai (2015), Moncrief (2017), Moncrief, Marshall, and Rudd (2015), Nunan, Sibai, Schivinski, and Christodoulides (2018), Oh (2017), Orozco (2016), Papp-Vary (2015), Rane, Mulla, Sarguru, and Sayed (2017), Roch and Mosconi (2016) The selected studies for the meta-synthesis are listed in Table 3. It can be observed that six of them were published in journals A1 (H Index > 24) and one classified as A2 (24 <= H Index < 9) according to the QUALIS from CAPES criteria, which indicates high-impact journals.…”
Section: Methodsmentioning
confidence: 99%
“…This eliminated another 18 studies (Table 2). Habibi, Hamilton, Valos, and Callaghan (2015), Hofacker, Malthouse, and Sultan (2016), Lin, Swarna, and Bruning (2017), Lindsey-Mullikin and Borin (2017), Marolt, Pucihar, and Zimmermann (2015), Ioanid, Militaru and Mihai (2015), Moncrief (2017), Moncrief, Marshall, and Rudd (2015), Nunan, Sibai, Schivinski, and Christodoulides (2018), Oh (2017), Orozco (2016), Papp-Vary (2015), Rane, Mulla, Sarguru, and Sayed (2017), Roch and Mosconi (2016) The selected studies for the meta-synthesis are listed in Table 3. It can be observed that six of them were published in journals A1 (H Index > 24) and one classified as A2 (24 <= H Index < 9) according to the QUALIS from CAPES criteria, which indicates high-impact journals.…”
Section: Methodsmentioning
confidence: 99%
“…The Ordering system is the system that stores the data about an order from the customer services employees or customer directly [2,3]. The data will be stored in the database and send the order information to the processing department.…”
Section: Ordering Systemmentioning
confidence: 99%